2012
DOI: 10.3171/2012.5.aospine12116
|View full text |Cite
|
Sign up to set email alerts
|

Translational potential of preclinical trials of neuroprotection through pharmacotherapy for spinal cord injury

Abstract: There is a need to enhance the pipeline of discovery and evaluation of neuroprotective pharmacological agents for patients with spinal cord injury (SCI). Although much effort and money has been expended on discovering effective agents for acute and subacute SCI, no agents that produce major benefit have been proven to date. The deficiencies of all aspects of the pipeline, including the basic science input and the clinical testing output, require examination to determine remedial strategies. Where has t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
33
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 82 publications
0
33
0
1
Order By: Relevance
“…eporting that a therapeutic effect exists when it does not (type I, alpha error) has major repercussions in acute traumatic spinal cord injury (tSCI) because of the lack of recognized treatment, 1 the relative desperation of the population, 2 and the substantial public sympathy and media interest that is mobilized around tSCI research. Promising pharmaceutical, medical, surgical, and rehabilitation interventions identified in preclinical studies heighten the expectations for subsequent clinical trials.…”
mentioning
confidence: 99%
“…eporting that a therapeutic effect exists when it does not (type I, alpha error) has major repercussions in acute traumatic spinal cord injury (tSCI) because of the lack of recognized treatment, 1 the relative desperation of the population, 2 and the substantial public sympathy and media interest that is mobilized around tSCI research. Promising pharmaceutical, medical, surgical, and rehabilitation interventions identified in preclinical studies heighten the expectations for subsequent clinical trials.…”
mentioning
confidence: 99%
“…Many therapeutic strategies have shown functional and histological improvements in animal models of SCI with only limited success in human clinical trials. 4 Riluzole, a neuroprotective drug licensed for the treatment of amyotrophic lateral sclerosis (ALS) patients, has also been tested in a rat model of SCI in a number of laboratories, including our own. 5,6 Riluzole acts on multiple molecular targets to improve functional recovery, although its mechanism of action has not been fully delineated.…”
Section: Introductionmentioning
confidence: 99%
“…Neuroprotective and neuroregenerative initiatives continue to evolve; however, no well-powered clinical trial has demonstrated an improvement in neurologic recovery and, therefore, these therapies have not been implemented in routine clinical practice. [1][2][3][4][5] A growing body of evidence suggests that timely surgical decompression and stabilization may improve neurological recovery by reducing secondary damage. [6][7][8][9][10] When one of the only interventions to potentially improve neurological outcomes in acute tSCI is early treatment, ensuring this knowledge is accepted and then translated into action is known as knowledge translation.…”
Section: Introductionmentioning
confidence: 99%